Konsep Perlindungan Anak Buah Kapal Perikanan Dalam Sistem Hukum Nasional - Muhamad Azhar; Suhartoyo Suhartoyo (Law, Development and Justice Review, 2022)
Abstract This study aims to find methods, solutions and explore the strengthening of the social security system for fishing crew workers in the framework of occupational risk protection and fair wage protection. In detail, the aims are to: formulate a model for strengthening the social security system for just fishing crew workers; designing a risk-based wage protection system for fishing vessel crews; and formulation of alternative policies for the protection of crew members of fishing vessels through national level regulations and regional regulations. The research method used in this research is legal research which is oriented towards policy reformulation produced by the government. This study uses a comparative approach and statutory approach. The object of research In the first year it was carried out on members of the Fishery Crew Labor Union of Central Java Province who are based in Tegal. In the second year, the crew of fishing vessels outside Java Island. The expected results of this research are that in the first year, it will produce a model for strengthening the social security system for fair fishing crew workers. in the second year, it will produce a design of a risk-based wage protection system for fishing vessel crew, a fishing vessel management system based on risk calculation and in the third year an alternative policy for protecting fishing vessel crew through national level regulations and regional regulations. Keywords: Ship's Crew, Fisheries, Employment, Social Security. Abstrak Penelitian ini bertujuan untuk menemukan metode, solusi dan mendalami penguatan sistem jaminan sosial bagi pekerja Anak Buah Kapal Perikanan dalam rangka perlindungan risiko kerja dan perlindungan upah yang berkeadilan. Secara terperinci bertujuan untuk: menformulasikan model penguatan sistem jaminan sosial bagi pekerja Anak Buah Kapal Perikanan yang berkeadilan; mendesain sistem perlindungan upah yang berbasis resiko bagi Anak Buah Kapal Perikanan; dan formulasi alternatif kebijakan perlindungan Anak Buah Kapal Perikanan melalui peraturan tingkat nasional dan peraturan daerah. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian hukum yang berorientasi pada reformulasi kebijakan yang dihasilakan oleh pemerintah. Penelitian ini menggunakan pendekatan comparative approach dan statutory approach. Objek penelitian Pada tahun pertama dilakukan terhadap Anggota Serikat Buruh Awak Kapal Perikanan Propinsi Jawa Tengah yang berdudukann di Tegal.  Hasil penelitian menujukan bahwa pada tahun pertama, menghasilkan model penguatan system jaminan sosial bagi pekerja anak buah kapal perikanan yang berkeadilan. pada tahun kedua, akan menghasilakan desain sistem perlindungan upah yang berbasis resiko bagi Anak Buah Kapal Perikanan, Sistem Penguhan yang berbasis pada perhitungan resiko dan pada tahun ketiga Alternatif kebijakan perlindungan Anak Buah Kapal Perikanan melalui peraturan tingkat nasional dan peraturan daerah. Kata Kunci: Anak Buah Kapal, Perikanan, Ketenagakerjaan, Jaminan Sosial.